Quand tout ne tient qu’à un pont ! Réfection d’ouvrage et dysfonctionnements urbains à Douala - Lourdes Diaz Olvera; Didier Plat; Pascal Pochet; Maïdadi Sahabana (Belgeo)
Rehabilitation work of the bridge on the Wouri river, in Douala, required the restriction of vehicle traffic, particularly taxis and motorbike taxis. To compensate for the reduction in public transport provision, a paying bus service for the crossing of the bridge was set up. The traffic restriction, imposed without forecasting side effects, revealed inconsistencies in institutional functioning and added on strong constraints to public transport users. Such an exceptional event shows evidence of the key role of large transport facilities in the functioning of African urban systems.